The late-Variscan peraluminous Valdepeñas pluton (southernCentral Iberian Zone) - J. Errandonea-Martin (Geologica Acta: an international earth science journal, 2017)
The Valdepeñas pluton is the easternmost outcrop of the Cáceres-Valdepeñas magmatic alignment (southern Central Iberian Zone). This massif is constituted by a cordierite-bearing porphyritic monzogranite and may be grouped within the so-called “Serie Mixta” granitoids. The Valdepeñas monzogranite is of magnesian [FeOt /(FeOt +MgO)~0.76], alkali-calcic [(Na2O+K2O)–CaO=7.8–8.5] and peraluminous (A/CNK=1.14–1.20) composition. Multielemental- and REE-normalized patterns are comparable to those of similar rocks in the NisaAlburquerque-Los Pedroches magmatic alignment, and slightly differ from those of the Montes de Toledo batholith, both in the southern Central Iberian Zone. The U-Pb zircon age of 303±3Ma is consistent with the late-orogenic character of the intrusion and is in accordance with most of the granitic peraluminous intrusions in the southern Central Iberian Zone. 86Sr/87Sr300Ma ratios (0.707424–0.711253), εNd300Ma values (-5.53 to -6.68) and whole-rock major and trace element compositions of the studied rocks, suggest that the parental magma of the Valdepeñas monzogranite could derive from a crustal metaigneous source. The U-Pb ages (552–650Ma) of inherited zircon cores found in Valdepeñas monzogranite samples match those often found in Lower Paleozoic metavolcanics and granitic orthogneisses of Central Iberia and, furthermore, point to Upper Neoproterozoic metaigneous basement rocks as possible protoliths at the magma source. Based on the solubility of monazite in peraluminous melts, the estimated emplacement temperature of the studied monzogranite is 742–762ºC. The results obtained in this work would contribute to a better understanding of the origin of the “Serie Mixta” granitoids.